Targeted Delivery of Pesticides Using Biodegradable Polymeric Nanoparticles - De, Arnab; Bose, Rituparna; Kumar, Ajeet; Mozumdar, Subho (SpringerBriefs in Molecular Science, 2014)
The brief is the first to focus exclusively on environmentally friendly delivery of pesticides (controlled-release nanoparticulate formulation of pesticides using biodegradable polymers as carriers). The brief also introduces pesticides like Chlorpyrifos and biodegradable polymers like guar-gum. The brief will be extremely useful to the researchers in the field of agrochemicals and will be equally useful for advanced professionals in the field of biology, chemistry, environmental biology, entomology and horticulture.